Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00264-016-3292-2
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of giant cell tumour of bone: role of p53, cyclin D1, β-catenin and Ki67

Abstract: This study confirmed independent predicting factors for GCTB reccurence: p53 expression in mononuclear tumour cells and cyclin D1 expression in giant multinuclear cells. Results are new addition to generally known parameters, such as: localization of lesion, number of surgical interventions, clear destruction of cortex with the presence of extracompartmental lesion, and histological criteria for malignancy and can help in further research and treatment of GCTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Histologically, osteoclast-like multinuclear giant cells and mononuclear neoplastic stroma cells influence tumor activity [1, 28], but histological classification of GCT was not reliable in predicting prognosis [5, 15, 29]. We also evaluated mitosis rate of the mononuclear cell population and found that higher mitosis rate was associated with significantly lower recurrence-free survival and higher hazard ratio in multivariate analysis, which is compatible with another report [21].…”
Section: Discussionsupporting
confidence: 80%
“…Histologically, osteoclast-like multinuclear giant cells and mononuclear neoplastic stroma cells influence tumor activity [1, 28], but histological classification of GCT was not reliable in predicting prognosis [5, 15, 29]. We also evaluated mitosis rate of the mononuclear cell population and found that higher mitosis rate was associated with significantly lower recurrence-free survival and higher hazard ratio in multivariate analysis, which is compatible with another report [21].…”
Section: Discussionsupporting
confidence: 80%
“…23 Other research groups had also reported various immunostaining factors (p53, cyclin D1, b-catenin, and Ki67 (MIB-1)) useful for predicting the recurrence of GCTB. 24,25 Therefore, to determine the utility of adjuvant therapy using denosumab in GCTB, the current study retrospectively analyzed the associations between recurrence status and clinicopathological factors, including denosumab and immunostaining factors, using 66 GCTB cases that occurred in the extremities, excluding the malignant ones.…”
Section: Brief Introductionmentioning
confidence: 99%
“…13,14,17,18 Recently, some researchers have identified some immunostaining factors (MIB-1, GPX-1, cyclin D1 and b-catenin) that are associated with predilection for GCTB recurrence. [19][20][21] This is all still experimental and has the potential for clinical use to determine cases that are more likely to recur. GCTB is different from Giant Cell Rich Malignancies where there is presence of giant cells in the malignant tumours.…”
Section: What Is Giant Cell Tumour Of the Bone (Gctb)mentioning
confidence: 99%